Pollen Evidence in Exploring Settlement Dynamics, Land Use, and Subsistence Strategies in the Aland Islands through Multiproxy Analyses from the Lake Dalkarby Trask Sediment Record - Alenius Teija; Ilves Kristin; Saarinen Timo (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
In this study, which presents pollen, charcoal, and 'soot'-particle records from a lacustrine sediment core, the development of the cultural landscape around Lake Dalkarby trask on the Aland Islands in Finland is scrutinised and discussed within a broad temporal setting in order to clarify the long-term interplay between the environment and human activities in this part of the archipelago. Special emphasis is given to the transition period from the Late Iron Age to medieval times due to the dominating humanistic discourse on the settlement dynamics in this region, as in the Aland archipelago in general, arguing for an approximately 150-years-long hiatus in habitation between these two periods, from AD 1050 to 1200. Our results do not support the hiatus theories but show a long and continuous history of the utilisation of land and forest resources starting from prehistoric times. The forests were first cleared with fire for slash-and-burn cultivation. Thereafter, structural diversity in the landscape started to increase. By 1240, the pollen data portrays a picture of a developed agrarian community with a subsistence economy based on arable farming and animal husbandry in which hemp seems to play a substantial part.